2020
DOI: 10.9758/cpn.2020.18.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation is Beneficial for Children with Autism Spectrum Disorder: A Meta-analysis

Abstract: Objective: We conducted a meta-analysis of randomized controlled trials to explore whether vitamin D supplementation is beneficial for symptom improvement in children with autism spectrum disorder. Methods: We systematically searched the PubMed database, EMBASE, Cochrane Library, Web of Science, Sino-Med, Wanfang Data, and China National Knowledge Infrastructure mainly up to September 2019. Using a fixed effects model, we calculated the standard mean difference with 95% confidence interval. Furthermore, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Interestingly, meta-analysis has shown that vitamin D3 800IU to 2,000IU supplementation improves core ASD symptoms as measured by the Social Responsiveness Scale or CARS in three studies in children with ASD who were not vitamin D deficient [104] and PQQ has been shown to improve social behavior in the bilateral whisker trimming for 10 days after birth in a mouse model which is characterized by its abnormal social behavior [105]. Thus, although no studies have been conducted in ASD or CFD to determine whether these supplements may improve function in children with ASD who have FRAAs or CFD, such supplements may have some utility in these children.…”
Section: Treatments That Support Folate Transport Into the Brainmentioning
confidence: 99%
“…Interestingly, meta-analysis has shown that vitamin D3 800IU to 2,000IU supplementation improves core ASD symptoms as measured by the Social Responsiveness Scale or CARS in three studies in children with ASD who were not vitamin D deficient [104] and PQQ has been shown to improve social behavior in the bilateral whisker trimming for 10 days after birth in a mouse model which is characterized by its abnormal social behavior [105]. Thus, although no studies have been conducted in ASD or CFD to determine whether these supplements may improve function in children with ASD who have FRAAs or CFD, such supplements may have some utility in these children.…”
Section: Treatments That Support Folate Transport Into the Brainmentioning
confidence: 99%
“…For example, Mazahery et al 12 showed that supplementation with vitamin D was superior over placebo in reducing irritability and hyperactivity 12 , while Kerley et al 13 did not find an effect of vitamin D on the severity of ASD symptoms 13 . Recently, Song et al 14 examined the efficacy of vitamin D supplementation in children with ASD through a meta-analysis 14 . However, it did not specially focus on symptoms of ASD such as social interaction, communication, and repetitive restrictive behaviors or interests (RRB) or symptoms or behaviors associated with ASD, including hyperactivity, irritability, and sensory issues.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study found significant benefits for many nutraceuticals with minimal adverse effects and are consistent with the findings of a number of clinical trials studying nutraceuticals in ASD. For example, double-blind, placebo-controlled studies, and/or meta-analyses have reported improvements in children with ASD using L-carnitine [ 32 , 33 ], Coenzyme Q10 (ubiquinone) [ 34 ], digestive enzymes [ 35 , 36 ], high dose folinic acid (1–2 mg/kg/day) [ 24 , 25 , 26 ], MB12 injections [ 37 ], melatonin [ 9 , 38 , 39 , 40 , 41 , 42 ], a multivitamin/mineral supplement designed specifically for ASD [ 26 , 27 ], NAC [ 29 , 43 , 44 , 45 ], omega 3 fatty acids [ 46 , 47 ], vitamin C [ 48 ], vitamin D3 [ 49 , 50 ], and possibly B6/Mg [ 51 , 52 ]. Open-label studies in ASD have also reported benefits for B vitamins [ 53 , 54 ], biotin [ 55 ], folic acid [ 56 ], an herbal formula [ 57 ], glutathione [ 58 ], iron [ 59 ], vitamin A [ 60 ] and zinc [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%